Study on theoretical modeling and mechanical performance of a spinning porous graphene nanoplatelet reinforced beam attached with double blades. Issue 8 (10th March 2023) - Zhao, Tian Yu; Jiang, Lu Ping; Yu, Yin Xin; Wang, Yan Qing
Abstract: In this article, theoretical modeling and vibration characteristics of a spinning double-blade beam assembly restricted by elastic supports are studied. Graphene nanoplatelet (GPL) reinforcement and porous foamed metal matrix are adopted to make up the assembly structure. Due to the nonuniformity of the porosity and graphene nanofillers, the material properties of the attached blades and beam are considered to change along the blade thickness and beam radius, respectively. They are obtained via the rule of mixture, the open-cell scheme and the Halpin-Tsai micromechanics model. These attached blades and beam are modeled in accordance with the Euler-Bernoulli beam theory and the Rayleigh beam theory, respectively. Via employing the Lagrange's equation, the equations of motion of the double-blade beam are derived. Then, the natural frequencies of the spinning nanocomposite double-blade beam are calculated by the substructure modal synthesis method and the assumed modes method. A detailed parameter analysis is performed to study the influences of dimension, distribution pattern and weight fraction of GPLs, distribution and coefficient of porosity, length and location of the blades, stiffness and location of supports, and spinning speed on the mechanical behaviors of the double-blade beam assembly.